Fairness, Control, and Counterproductive Behavior: A Study of Contract Employees - Ferdyandhika, Lutfi Fitra; Pertiwi, Talitha Lintang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This study aimed to analyze the influence of Organizational Justice on Counterproductive Work Behavior (CWB) among contract employees, with Locus of Control as a moderating variable. Contract employees are vulnerable to job uncertainty, which may trigger counterproductive work behavior. The research method used was quantitative with a causal comparative (ex-facto) approach. The subjects were 171 contract employees selected using the purposive sampling. Data collection was conducted online using the Organizational Justice Scale, Counterproductive Work Behavior Scale, and IPC Scale to measure internal and external Locus of Control. Data analysis utilized simple linear regression and Moderated Regression Analysis (MRA). The results show that Organizational Justice has a negative and significant influence on Counterproductive Work Behavior (Estimate = -0.166; p = 0.030). The MRA results indicate that internal Locus of Control weakens (Estimate = 0.0547; p = 0.025) 10and external Locus of Control strengthens (Estimate = -0.0369; p = 0.002) the negative influence of Organizational Justice on Counterproductive Work Behavior. This finding emphasizes that the role of Organizational Justice in suppressing CWB significantly depends on the individual's Locus of Control personality characteristic.Penelitian ini bertujuan untuk menganalisis pengaruh Organizational Justice terhadap Counterproductive Work Behavior (CWB) pada karyawan kontrak, dengan Locus of Control sebagai variabel moderator. Karyawan kontrak merupakan kelompok yang rentan terhadap ketidakpastian kerja yang berpotensi memicu munculnya perilaku kerja kontraproduktif. Jenis penelitian yang digunakan adalah kuantitatif dengan pendekatan kausal komparatif (ex-facto). Subjek penelitian adalah 171 karyawan kontrak yang diambil menggunakan teknik purposive sampling. Pengumpulan data dilakukan secara daring menggunakan Organizational Justice Scale, Counterproductive Work Behavior Scale, dan IPC Scale untuk mengukur Locus of Control internal dan eksternal. Analisis data menggunakan regresi linier sederhana dan Moderated Regression Analyze (MRA). Hasil penelitian menunjukkan bahwa Organizational Justice berpengaruh negatif dan signifikan terhadap Counterproductive Work Behavior (Estimate = -0,166; p = 0,030). Hasil MRA menunjukkan bahwa Locus of Control internal melemahkan (Estimate = 0,0547; p = 0,025) dan Locus of Control eksternal memperkuat (Estimate = -0,0369; p = 0,002) pengaruh negatif Organizational Justice terhadap Counterproductive Work Behavior. Temuan ini menekankan bahwa peran Organizational Justice dalam menekan CWB sangat bergantung pada karakteristik kepribadian Locus of Control individu